ANALISIS STRATEGI DAN KONTROVERSI MULTI LEVEL MARKETING: PROBLEM SOLVING DALAM KONTEKS EKONOMI SYARIAH - NURHAM, MUH; KIRANA, AYU PUSPA; AMIR, MUHAMMAD FAKHRI (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Multi Level Marketing system provides benefits for various parties, including entrepreneurs, both producers and Multi Level Marketing companies. A very controversial thing in this business is that prospective members who want to join are required to first buy goods so that the purchased goods will later be marketed again and by providing work motivation to members to recruit members to increase the distribution network of goods. The writing of this article uses a qualitative research design in the form of Library Research, using data collection techniques through journals and related books. The results of this study indicate that Multi Level Marketing Business can be considered haram if the product is only used as a tool to get bonuses, because commissions in the Multi Level Marketing system often depend on downline performance. Although the model agreement may be declared valid, another problem that arises is the willingness of downline members to join. However, because he wants to become a member and must meet the requirements to buy the product first, the prospective member is forced to buy it. Transactions like this are considered haram if the goal is more for sales or recruitment bonuses than for the product itself.